Brain correlates of pro-social personality traits: a voxel-based morphometry study - Coutinho, Joana (2013)
Of the five personality dimensions described by the Big Five Personality Model (Costa and McCrae 1992), Extraversion and Agreeableness are the traits most commonly associated with a pro-social orientation. In this study we tested whether a pro-social orientation, as expressed in terms of Extraversion and Agreeableness, is associated with a specific grey matter phenotype. Fifty-two healthy participants underwent magnetic resonance imaging (MRI) and completed the NEO-Five Factor Inventory (NEO-FFI), a self-report measure of the Big Five personality traits. Voxel-based morphometry (VBM) was used to investigate the correlation between brain structure and the personality traits of Agreeableness and Extraversion. We found that Extraversion was negatively correlated with grey matter density in the middle frontal and orbitofrontal gyri while Agreeableness was negatively correlated with grey matter density in the inferior parietal, middle occipital and posterior cingulate gyri. No positive correlations were found. These results suggest that pro-social personality traits seem to be associated with decreases in grey matter density in more frontal regions for Extraversion, and more posterior regions for Agreeableness.